Combined assessment of stress cardiovascular magnetic resonance and angiography to predict the effect of revascularization in chronic coronary syndrome patients. (23rd October 2021) - Gavara, Jose; Perez, Nerea; Marcos-Garces, Victor; Monmeneu, Jose V; Lopez-Lereu, Maria P; Rios-Navarro, Cesar; De Dios, Elena; Bonanad, Clara; Cánoves, Joaquim; Moratal, David; Palau, Patricia; Miñana, Gema; et al.
Abstract: Aims: The role of revascularization in chronic coronary syndrome (CCS) and the value of ischaemia vs. anatomy to guide decision-making are in constant debate. We explored the potential of a combined assessment of ischaemic burden by vasodilator stress cardiovascular magnetic resonance (CMR) and presence of multivessel disease by angiography to predict the effect of revascularization on all-cause mortality in CCS. Methods and results: The study group comprised 1066 CCS patients submitted to vasodilator stress CMR pre-cardiac catheterization (mean age 66 ± 11 years, 69% male). Stress CMR-derived ischaemic burden (extensive if >5 ischaemic segments) and presence of multivessel disease in angiography (two- or three-vessel or left main stem disease) were computed. The influence of revascularization on all-cause mortality was explored and adjusted hazard ratios (HRs) with the corresponding 95% confidence intervals were obtained. During a median 7.51-year follow-up, 557 (52%) CMR-related revascularizations and 308 (29%) deaths were documented. Revascularization exerted a neutral effect on all-cause mortality in the whole study group [HR 0.94 (0.74–1.19), P = 0.6], in patients without multivessel disease [ n = 598, 56%, HR 1.12 (0.77–1.62), P = 0.6], and in those with multivessel disease without extensive ischaemic burden [ n = 181, 17%, HR 1.66 (0.91–3.04), P = 0.1]. However, compared to non-revascularized patients, revascularization significantly reduced all-cause mortality in patients with simultaneous multivessel disease and extensive ischaemic burden ( n = 287, 27%): 3.77 vs. 7.37 deaths per 100 person-years, HR 0.60 (0.40–0.90), P = 0.01. Conclusions: In patients with CCS submitted to catheterization, evidence of simultaneous extensive CMR-related ischaemic burden and multivessel disease identifies the subset in whom revascularization can reduce all-cause mortality. Graphical Abstract: